Simulating consistency effects and individual differences in nonword naming: a comparison of current models. - Zezin JD; Seidenberg MS (Journal of Memory & Language, 2006)
The mechanisms underlying nonword pronunciation have a been a focus of debates over dual-route and connectionist models of reading aloud. The present study examined two aspects of nonword naming: spelling-sound consistency effects and variability in the pronunciations assigned to ambiguous nonwords such as MOUP. Performance of a parallel distributed processing model was assessed over multiple runs, representing multiple subjects with varying reading experience. The model provided a good account of behavioral data concerning these phenomena. In contrast, the Dual Route Cascaded model does not produce consistency effects and does not account for the alternative pronunciations that subjects produce. The results highlight the importance of considering multiple aspects of a phenomenon such as nonword naming in assessing computational models.